Higher perfusion pressure and pump flow during cardiopulmonary bypass are beneficial for kidney function–a single-centre prospective study - Udzik, Jakub; Pacholewicz, Jerzy; Biskupski, Andrzej; Safranow, Krzysztof; Wojciechowska-Koszko, Iwona; Kwiatkowski, Paweł; Roszkowska, Paulina; Rogulska, Karolina; Dziedziejko, Violetta; Marcinowska, Zuzanna; Kwiatkowski, Sebastian; Kwiatkowska, Ewa (Frontiers in Physiology, 2024)
Background: Kidneys play an essential role in the circulatory system, regulating blood pressure and intravascular volume. They are also set on maintaining an adequate filtration pressure in the glomerulus. During the CPB, a decrease in systemic blood pressure and hemoglobin concentration may lead to renal ischemia and subsequent acute kidney injury.Methods: One hundred nine adult patients were prospectively enrolled in this study. The intervention in this study was increasing the flow of the CPB pump to reach the target MAP of > 90 mmHg during the procedure. The control group had a standard pump flow of 2.4 l/min/m 2 .Results: Standard pump flow of 2.4 l/min/m 2 resulted in mean MAP < 90 mmHg during the CPB in most patients in the control group. Maintaining a higher MAP during CPB in this study population did not affect CSA-AKI incidence. However, it increased the intraoperative and postoperative diuresis and decreased renin release associated with CPB. Higher MAP during the CPB did not increase the incidence of cerebrovascular complications after the operation; patients in the highest MAP group had the lowest incidence of postoperative delirium, but the result did not obtain statistical significance.Conclusions: Maintaining MAP > 90 mmHg during the CPB positively impacts intraoperative and postoperative kidney function. It significantly reduces renal hypoperfusion during the procedure compared to MAP < 70 mmHg. MAP > 90 mmHg is safe for the central nervous system, and preliminary results suggest that it may have a beneficial impact on the incidence of postoperative delirium.Introduction: Since the introduction of the cardiopulmonary bypass (CPB) technique in 1952, there has been an ongoing debate on the optimal conditions